7T Small Animal MRI Research for Hepatic Alveolar Echinococcosis. Issue 6 (December 2022) - Zhang, Guanmi; Mou, Yalin; Fan, Haining; Li, Weixia; Cao, Yuntai; Bao, Haihua
Abstract: Objectives: 7T small animal magnetic resonance imaging (MRI) was used to analyze the growth characteristics of hepatic alveolar echinococcosis (HAE). Methods: A mouse model of HAE was established by intraperitoneal injection of alveolar Echinococcus tissue suspension. Ten mouse models successfully inoculated by ultrasound screening were selected. The mouse model was scanned with T1-weighted imaging (T1WI), T2-weighted imaging (T2WI), and diffusion-weighted imaging (DWI) sequence by 7T small animal MRI. Size, morphology, boundary, signal, and relationship with surrounding tissues of the lesions were recorded as characteristic alterations. Mice were killed at the end of the experiment, and the pathological specimens were taken for routine hematoxylin and eosin staining. Results: Lesions were mainly located in the right lobe of the liver. The multivesicular structure is the characteristic manifestation of this disease. In the liver, lesions invaded the portal vein and were mainly distributed at the hepatic hilum. The left branch of the portal vein was mainly invaded. The mean diameter of the lesions in the left lobe of the liver was larger than in other parts of the liver. The mean diameter of the cystic solid lesions was greater than the multilocular cystic lesions. HAE showed hypointense on T1WI, hyperintense on T2WI, and hypointense on DWI; the marginal zone of the lesion showed hyperintensity on DWI and grew toward the hilum. The MRI features of intraperitoneal lesions were similar to those of intrahepatic lesions. Intraperitoneal lesions increased faster than intrahepatic lesions in the same period. Conclusion: Polyvesicular structure is a characteristic manifestation of hepatic alveolar echinococcosis in mice. The noninvasive monitoring of liver HAE in mice by 7T small animal MRI provides a visual basis for the diagnosis and treatment integration of HAE.